PREPARATION AND ANALYSIS OF THE NMR SPECTRA OF THE PHARMACEUTICAL SUBSTANCEÂ«OOSE-11,12,13Â» - K, BERKENOV; Um, Datkhayev (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The main issue of this work is obtained, to researching of supramolecular complexes of 20-hydroxyecdysone (20 E) with Î³-cyclodextrins (CD). Methods: The foundation of substance phytoecdysteroid 20 E was isolated from an ethanol extract plant Otites orae-syvaschicae Klok A method of the development of pharmaceutical substances was used during complexed organic relationship in the way of intense mechanical 20 E with Î±-, Î²- or Î³-Ð¡D. The complexation of 20 E with Î±-, Î²-, and Î³-Ð¡D was studied by nuclear magnetic resonance (NMR) method of spectr Results: In the study of the integrated intensities molecules signals steroid guest and host CD complex stoichiometric ratio 1:1 was prformation of clathrates was established after A and B nuclei ecdysterone had been arranged in the internal cavity of CD. Ð¡onclusion: Supramolecular complexes of 20 E with Î±-, Î²-, and Î³-Ð¡D were received during made works. The objects of research were analdescribed with the help of NMR spectroscopy. The developed technology will be the main device for operating and identification of pharmaceutical substance OOSE-11, -12, and -13. Keywords: Substance Otites orae-syvaschicae Klok-11, -12, -13, 20-hydroxyecdysone, Î±-, Î²-, Î³-cyclodextrins inclusion complex nuclear resonance spectroscopy.